A friend is a treasure: emotional intelligence, workplace social support and teacher engagement (2019)
This research examines the relationship among emotional intelligence, workplace social support from colleagues and supervisors, and work engagement in a sample of 110 Spanish primary and secondary teachers. The results showed that emotional intelligence was not related to perceived support from colleagues or supervisors. However, both emotional intelligence and social support from colleagues and supervisors showed significant positive associations with teacher engagement. Moreover, moderation analyses showed that main effects of emotional intelligence and social support from colleagues—not support from supervisors—explained significant variance in teacher engagement. Finally, the interaction of both personal—emotional intelligence—and job—social support from colleagues and supervisors—resources added incremental variance to the explanation of teacher engagement. Overall, our findings underline that educational administrations should take efforts in designing emotional intelligence intervention programs for teachers as well as creating collaborative and supportive environments facilitating development of teacher engagement.